PENGARUH KEBERADAAN WISATAWAN ASING TERHADAP PERKEMBANGAN BISNIS PARIWISATA MASYARAKAT DI TUKTUK SIADONG - Grace Berlian Sinambela (Perspektif Sosiologi, 2012)
ABSTRACT Tuktuk Siadong has become a recreational area since 1960. Tuktuk as one of the most famous tourism destination in North Sumatra makes Tuktuk not only visited by local tourist, but also foreigner. In Tuktuk, most of people use Batak as their main language, and English or other foreign language as their secondary languages, but only a few of them can speak Indonesia well. Indirectly, we can say that the local condition is still maintained, but nationality is abandoned. It is good to keeping traditionality, as Dove said, it’s a supporting factor of development. But we should remember that national language however should be mastered. This research also find that most of local people start changing their couple preference, preferring foreigner to their fellow local. It caused beside their thought that people who marry foreigner having a higher social status, also by their desire to evolve their business, asset and some.   Keywords: Foreign tourism existence, Tuktuk Siadong.